EVALUASI BAHAN BAKU INDUSTRI ARANG DI KESATUAN PEMANGKUAN HUTAN (KPH) TANJUNG PINANG - Boen M Purnama; Subandi Subandi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The appraisal of charcoal raw material was conducted in Tanjung Pinang, Province of Riau. The study showed that Bakau (Rhizophora sp.) is the only species used for charcoal making, whereas, Nyirih (Xylocarpus sp.) is widely used as starting fuel. The amount of bakau wood required per kiln per batch was 71.1ton. Rough estimate on total bakau wood required per year was 178,515 cu.m., while available raw material only 43,181 cu.m/year. There seems to be a remarkable shortage of raw material of this time. Most of the charcoal manufacturer, at the time of survey, adjust the production capacity by reducing the number of operation or by obtaining new raw material from neibouring areas